Efficiency of South African municipalities in utilising infrastructure assets in addressing water and electricity service delivery challenges. - Govinden, Krisseelan (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.